Determinants of Cash Waqf Linked Sukuk Investment Preference: The Role of Religiosity, Income, and Reputation in East Java Millennials - Ananta Putri Sandrina; Ramdani Ramdani (International Conference on Islamic Economic (ICIE), 2026)
Waqf assets are predominantly developed into physical buildings, while a considerable proportion remains underutilized as idle land, limiting their socio-economic potential. Although Cash Waqf Linked Sukuk (CWLS) has emerged in Indonesia as an innovative Islamic financial instrument supporting education, healthcare, and sustainable social infrastructure, public participation, particularly among millennials, remains relatively low. Therefore, this study aims to examine the influence of religiosity, income level, and institutional reputation on millennials’ investment interest in CWLS in East Java. This study employed a quantitative approach using survey data collected from 140 millennial respondents. Multiple linear regression analysis was applied to test the relationships among variables. The findings reveal that religiosity and income level do not significantly affect investment interest, whereas institutional reputation exerts a positive and significant influence. The coefficient of determination (R² = 0.663) indicates that 66.3% of investment interest is explained by the proposed variables. This study contributes by highlighting the strategic importance of institutional credibility, Islamic financial literacy, and Sharia compliance in strengthening public trust and promoting CWLS participation